Stability Exercise Reduces Pain and Improves Function in Postpartum Lumbo-Pelvic Pain: A Systematic Review - Fuja Setia Ningrum; Viskasari Pintoko Kalanjati ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2026)
Background: Postpartum lumbo-pelvic pain (LPP) is a common musculoskeletal problem that may persist for several months after childbirth and interfere with maternal function. Stability exercise, focusing on deep core muscles, has been suggested as a non-pharmacological approach; however, the evidence remains scattered.Methods: A systematic review was carried out following PRISMA 2020 guidelines. Electronic databases (PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar) were searched for studies published between March 2015 and December 2024. Eligible studies included postpartum women (≤ 6 months) with LPP, comparing stability/core-focused exercise with conventional care or other exercise modalities. Primary outcomes were pain intensity measured using the Visual Analogue Scale (VAS) and functional disability assessed by the Oswestry Disability Index (ODI). Quality assessment of included papers was performed using the JBI tools. Data were extracted independently and analyzed narratively. Results: Three randomized controlled trials enrolling a total of 130 postpartum women with lumbopelvic pain were included. Intervention protocols varied from 6 to 12 weeks, with 3–5 sessions per week. All studies consistently reported greater reductions in pain scores in the stability exercise groups compared with control groups. Two studies additionally found significant improvements in functional disability (ODI) following stability training.Conclusion: Stability exercise appears effective in alleviating pain and improving function in postpartum women with LPP. Its integration into postpartum rehabilitation programs may provide a safe, accessible, and beneficial alternative to conventional management strategies. Further large-scale trials are needed to confirm optimal protocols and long-term outcomes.